Perbandingan tumpukan beras Bulog terhadap populasi kutu beras (Sitophilus oryzae L.) dan mutu beras selama masa simpan di Kabupaten Jayawijaya - Anti Uni Mahanani; Inrianti (Universitas Lancang Kuning, 2021)
This study was aimed to find out the effect of rice pile on pest population and the quality of rice during storage; find out which pile of Bulog rice produces the populations of Rice Weevil pest the most during storage; find out which pile of Bulog rice that produces the best quality during storage. This research was conducted in the laboratory of STIPER Petra Baliem Wamena and the Faculty of Agricultural, Universitas Gadjah Mada Yogyakarta. The observation was done in 1 year, from March 2019 to March 2020. The materials and tools used are Bulog rice, rice weevil pest, cartons, plastics, digital scales, stationary, and oven. The research method applies a Completely Randomized Design. The treatments are G1: 15 Bulog rice pile; G2: 20 Bulog rice pile; G3: 25 Bulog rice pile. The results showed that: 1) The rice pile affected the pest population and the quality of rice during storage; 2) G3 condition produced more rice weevil population than others; 3) G1 condition produced the highest final weight of rice, the lowest broken rice, the highest intact rice, the lowest water content, and ash content, and the highest fat content, protein content, and carbohydrate content.